Changes in potential pathogenicity-associated proteins of Helicobacter cinaedi upon infection of macrophage cells - Voronina, A. K.; Efimov, B. A.; Malakhova, M. V.; Shnaider, P. V.; Ivanova, O. M.; Bogomiakova, M.; Shender, V. O.; Lagarkova, M. A.; Arapidi, G. P. (Frontiers in Microbiology, 2025)
IntroductionHelicobacter cinaedi is a spiral-shaped Gram-negative, enterohepatic bacterium classified as a conditional pathogen (pathogenicity group 2). It is known to cause bacteremia and a variety of other diseases in humans. In particular, Helicobacter cinaedi has been shown to impair intracellular cholesterol metabolism when interacting with macrophages, leading to foam cell formation. M1-macrophages transformed into the foam cell phenotype contribute to atherosclerotic plaques, suggesting a potential link between H. cinaedi infection and atherosclerosis development.MethodsTo uncover protein factors involved in H. cinaedi pathogenesis, we performed a detailed mass spectrometric analysis of the proteome of strain BAA-847. This study represents the first comprehensive analysis of the bacterium’s proteome under standard culture conditions and after infection of M1-type macrophage cells.ResultsWe identified 1,575 proteins in the H. cinaedi proteome, 109 of which were differentially upregulated after macrophage infection. Functional analysis revealed roles for these proteins in immune evasion, intracellular survival, and potential pathogenicity. Beyond known virulence factors (HcaA, Cdt, AhpC), we identified poorly characterized proteins with toxic or immunomodulatory functions. Notably, some upregulated proteins enable cholesterol utilization as a carbon source, while others may participate in a toxin injection mechanism disrupting host cell metabolism—potentially linked to foam cell formation.ConclusionOur findings provide new insights into H. cinaedi pathogenicity, highlighting previously unexplored virulence mechanisms. The identified proteins could serve as targets for further research into H. cinaedi-associated diseases, including atherosclerosis.